THE INNOVATIVE CONSUMPTION AS A MODERN ECONOMIC BEHAVIOR (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article considers the innovative consumption as the modern consumer’s economic behavior being viewed herein through the essence of its definition, as well as through the motivation character of the modern consumer of goods and services within the consumption updating. Moreover, the innovative consumption is a challenge of the modern world, as well as the conscious and responsible demand generation, the guarantee of the environmentally and friendly maintenance of the production and resource use, and the assistance in the alternative promising ways for the efficient production and responsible profitability.The motivation of consumer’s innovations is a set of needs and motives encouraging consumers to active activities towards the innovative renewal of their behavior based on scientific and technological progress and the use of innovations. It is reached through the purchase of innovative products and their use for the conscious and responsible consumption as the final phase of the social production and component of every business process.The motivation is considered in the innovative consumption as the choice of methods and directions of operations of motive forces (motives). The last-mentioned are involved to achieve our goals and responsibility for all the previous manufacturers’ and sellers’ actions, their behavior on the market and the impact of the implementation of the goal on the further development of the scientific and technological progress, innovation and eco-friendly environment. The motivation of consumer innovations should be considered in two vectors: 1) the motivation to support the creation of production of innovations that meet the needs of modern demand and affordable sales of these innovations and 2) the motivation to understand these innovations, the conscious purchase and consumption of these innovations.The innovative consumption is one of the important tools for creating a solvent demand for innovations. This leads economic entities, as the main collective consumers of innovations, to produce, to consume and to work with innovations. Moreover, they may demand and participate in the development of technology and high technologies, raising standards and quality of the life through a quantitative and qualitative change in the factors causing its growth, namely, a multiple increase in the share of products received from the innovation.The following ways have been proposed for forming a balance of innovative processes in the production and consumption, ensuring the necessary volume of effective demand for innovations and innovative products:• The encouragement concerning the exchange of innovations and innovative products through the import of innovations and export of domestic innovations from other countries and in our country, to expand those who own new technologies or ideas for their production, creating conditions for increasing investment resources that will provide support for an effective domestic innovation investment process. The exchange of innovations and the results of using innovative products contributes to the establishment of innovative behavior of producers and consumers, maintaining solvent innovative demand.• The assurance of the accessibility and predictability of investment resources and their cost in the state, which will stimulate direct and indirect instruments to force institutions and organizations to resource- and energy-saving, environmentally friendly, modern high-tech technologies, as well as to the innovative management and organization of economic activity. The predicted value of investment and innovative resources will ensure the expected, efficient and responsible use of investment resources and increase innovative products.• The promotion of mechanisms: the economic behavior of producers and consumers as the innovative behavior, and the formation of sustainable innovative interests.• The assistance in the formation and implementation of the state innovation programs, national innovation projects, targeted innovation development programs of territorial communities.• The formation of the innovative demand in the form of consumption patterns of new, more advanced goods and services inherent in countries with developed market economies and growing consumer cultures.• The reorientation of the socio-economic activity of consumers at the micro level in order to increase or expand the consumption to increase the consumption of innovations and innovative products as a subject of innovative development for the development of the economy and society.This will ensure the formation of the balanced innovative processes in the production and consumption, in their consistency and simultaneity, and will form the necessary volume of the solvent demand for the innovation and innovative products. The state assistance forms listed herein will become the basis for the formation of the necessary and sufficient volume of the solvent demand for innovations through the mechanisms of the investment and innovative behavior. That will be approved as a progressive, correct and mutually beneficial innovative development in the economy, ensuring the Ukrainian economy development as an innovative type of economy, not only by the growth of the investment, but also primarily innovation activity of economic entities.
Keywords: innovative consumption, consumption motivation, consumer motivation updating, consumer’s economic behavior, economic behavior of the consumer of innovative goods and services.